Captain Flinn and the pirate dinosaurs : missing treasure! - Andreae, Giles, 1966- (Margaret K. McElderry Books, 2008)
On a school field trip to the museum, young Captain Flinn and his crew recover a museum treasure from a dastardly group of pirate dinosaurs.